Anxiolytic and antidepressant effects of cannabidiol: a systematic review - Honório Júnior, José Eduardo Ribeiro; Barriga, Jessica Rodrigues de Morais; Mesquita, Dara da Silva; Pinto, Joel Porfírio (Journal of Health & Biological Sciences, 2021)
Objetctive: Realize a systematic review on articles about cannabidiol (CBD) as an anxiolytic and antidepressant drug. Methodology: A systematic review in PubMed, Science Direct and PsycINFO databases taking into consideration articles published in English and Portuguese from 2008 to 2018 with animal experimentation. Results: Eleven articles with experimental studies on animals were included. All studies exhibited anxiolytic and antidepressant activities after CBD use. Conclusion: It was proven by several experiments the anxiolytic and antidepressant activity of CBD, however there is still a need of more preclinicals and clinicals studies to elucidate its mechanisms.